2018
DOI: 10.5530/pj.2018.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro Antidiabetic and Antioxidant Activity of Various Extracts of Ficus Species

Abstract: Introduction:Ficus religiosa, Ficus benghalensis and Ficus glomerata are plants from Ficus species used traditionally for the treatment of various ailments. This study aimed to investigate in vitro antidiabetic and antioxidant activity of three plants from Ficus species and effect of extracting solvents, total flavonoids and phenolics content on its in vitro activity. Methods: Dried leaf powder was extracted successively by using solvents with increasing order of polarity index (PI). In vitro antioxidant (RP: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This result is in line with some previous reports with other plants. 2,49 –52 The aqueous-methanol fraction may contain compounds that are structurally analogous to the natural substrates of the enzymes like phenolics, flavonoid glycosides, and saponins and could interfere with the normal activity of the enzymes. The extracts showed a relatively higher inhibition of glucosidase, an indication that they may have a relative advantage of lesser or no side effects compared to the standard drug.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with some previous reports with other plants. 2,49 –52 The aqueous-methanol fraction may contain compounds that are structurally analogous to the natural substrates of the enzymes like phenolics, flavonoid glycosides, and saponins and could interfere with the normal activity of the enzymes. The extracts showed a relatively higher inhibition of glucosidase, an indication that they may have a relative advantage of lesser or no side effects compared to the standard drug.…”
Section: Discussionmentioning
confidence: 99%
“…Isophthalic acid Antidiabetic (Patel et al, 2016); (Acta, 2021); (Choudhary et al, 2011), alpha-amylase and alpha glucosidase inhibitors (Rajan, 2017), antidiabetic and antioxidant (Abusufyan et al, 2018)…”
Section: Identified Compoundsmentioning
confidence: 99%
“…The Penicillium TR3 strain displayed significant α-amylase inhibitory activity with an inhibition rate of 96.34%. They separated and identified several compounds, and compound 27 (oleic acid; Ahmad et al, 2012 ; Indrianingsih et al, 2018 ), compound 28 (1,3-benzenedicarboxylic acid, bis (2-ethylhexyl) ester, isophthalic acid group; Rajan and Aanandhi, 2017 ; Abusufyan et al, 2018 ), compound 29 (hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl) ethyl ester (CAS), palmitin group; Venkatramanan et al, 2020 ) showed inhibitory activities against α-glucosidase and α-amylase ( Siregar et al, 2022 ).…”
Section: Inhibitors Of Glycosidases From Different Microbesmentioning
confidence: 99%